Hutang perusahaan dan sektor kehutanan Indonesia - Barr, C.; Brown, D.; Casson, A.; Kaimowitz, D. (Yayasan Obor Indonesia, 2003)
The Indonesian Bank Restructuring Agency (IBRA) holds US$ 4.1 billion in loans related to forest and estate crop activities, of which US$ 2.7 billion are nonperforming. Ten large conglomerates account for over 70% of the bad forest and estate crop debt. These groups are also responsible for some US$ 2.4 billion in domestic nonperforming loans in other sectors and US$ 15 billion in offshore debt. The current high level of non-performing loans stems, in large part, from the failure by banks to exercise due diligence (i.e., seriously assess the potential for loan default) when Indonesia’s forest-linked conglomerates sought to borrow funds prior to the crisis. Direct government subsidies for forest and estate crop activities also encouraged corporate risk taking. Strong evidence suggests that debt write-offs and loan restructuring may provide Indonesia’s forest-related industries with a substantial capital subsidy. This study projects that IBRA will eventually write-off US$ 1.3 – 1.9 billion of debts associated with timber, wood processing, pulp and paper, and oil palm investments. Debt write-off on this scale, together with IBRA’s current lack of supervision over the forest-related companies that owe it large sums of money, will serve as an impetus for debtor firms to continue to engage in practices involving an inordinate degree of financial risk.